Genomic identification of two hare species (Lepus timidus, L. europaeus) and their hybrids using a novel panel of genomic loci: MIPs (Multi-locus Intron Polymorphisms) - Marinangeli, L.; Boscari, E.; Scapolatiello, A.; Crestanello, B.; Galla, G.; Nonnis Marzano, F.; Ferloni, M.; Congiu, L.; Hauffe, H. C. (country:IE, 2024)
The mountain hare (Lepus timidus) is an arctic-alpine species, with relictual populations in the Alps threatened by climate and anthropic changes that result in snow cover reduction and habitat loss, as well as resource competition and hybridization with the European brown hare (L. europaeus). The latter is a typical species of open habitats in agricultural landscapes, often restocked for hunting and with an Alpine distribution currently shifting into areas once dominated by the mountain hare, due to an increase in mean winter temperatures. For conservation and management purposes, we developed a new panel of Multi-locus Intron Polymorphisms ('MIPs') for mammalian genomic surveys, species and individual identification, and monitoring of interspecific hybridization, with a specific subset for L. timidus, L. europaeus and their hybrids. To generate the mammalian panel, a total of 121 genomes were aligned to identify the most conserved intronic regions and 192 introns randomly distributed across the genomes were then selected. Primer pairs suitable for multiplex PCR amplifications followed by Illumina amplicon sequencing were designed on conserved exonic flanking regions. The MIPs panel was tested on tissue samples from 260 mountain and 70 brown hares bagged in the Province of Sondrio (Italy), from three hunting areas with different intensities of L. europaeus restocking; in addition, two altitudinal ranges (below and above 2000m a.s.l.) and two collection periods (2001-2008 and 2016-2023) were considered as proxies for climate change scenarios. Amplicon sequencing data were analysed with dedicated bioinformatic pipelines to assess inter- and intraspecific genetic diversity and level of hybridization of the populations under study. Our work highlights the impact of L. europaeus restocking and climate on L. timidus genomic diversity, and we discuss the usefulness of MIPs for guiding conservation strategies